Mesenchymal Stem Cells Transplantation in Intracerebral Hemorrhage: Application and Challenges - Gong, Yu-hua; Hao, Shi-lei; Wang, Bo-chu (Frontiers in Cellular Neuroscience, 2021)
Intracerebral hemorrhage (ICH) is one of the leading causes of death and long-term disability worldwide. Mesenchymal stem cells (MSCs) therapies have demonstrated improved outcomes for treating ICH-induced neuronal defects, and the neural network reconstruction and neurological function recovery were enhanced in rodent ICH models through the mechanisms of neurogenesis, angiogenesis, anti-inflammation and anti-apoptosis. However, many key issues associated to the survival, differentiation and safety of grafted MSCs after ICH remain to be resolved, which hinder the clinical translation of MSCs therapy. Herein, we reviewed an overview of the research status of MSCs transplantation after ICH in different species including rodents, swine, monkey and human, and the challenges for MSCs-mediated ICH recovery from pathological microenvironment have been summarized. Furthermore, some efficient strategies for the outcome improvement of MSCs transplantation were proposed.